Synergistic effects of an Ethanol-Diethyl Ether biofuel blend on biodiesel-based dual-fuel combustion: A comparative injection strategy study - Firat, Mujdat; Batmaz, Bahar (Pergamon-Elsevier Science Ltd, 2026)
This study presents a comprehensive investigation into optimizing a diesel engine powered entirely by 100% renewable liquid biofuels through a comparative injection strategy analysis. In this context, the effects of using biodiesel, ethanol, and diethyl ether, which are alternative fuels, on combustion and pollutant emissions in a diesel engine were experimentally investigated under different injection strategies and advanced low-temperature combustion based dual-fuel strategies. A single-cylinder diesel engine was used in the experiments. While biodiesel was directly injected into the engine with a high-pressure fuel injection system, ethanol or diethyl ether-blended ethanol was injected using both port and dual-direct injection methods. Experimental studies were conducted at engine loads corresponding to 25%, 50%, and 75% of the maximum engine load, at a constant engine speed of 2400 rpm. First, biodiesel-ethanol and biodiesel-ethanol-diethyl ether mixtures prepared according to different energy contents were injected using the port injection strategy. Subsequently, the same procedures were performed using the dual-direct injection strategy following the same sequence. According to the obtained results, it was observed that the fuels added to biodiesel increased CO emissions at 25% and 50% engine loads regardless of injection strategy and ratio, but reduced them at 75% engine load. For HC emissions, regardless of injection strategy and ratio, reductions of up to 60% were achieved for low-temperature combustion conditions as the proportion of diethyl ether added to ethanol increased and as the engine load increased across all engine loads. At low and medium engine loads, a decrease in NO emissions was observed under more effective low-temperature combustion conditions. A general decrease in smoke opacity was observed for all engine loads and fuel ratios compared to biodiesel. Reductions of up to 86% in smoke opacity, which is considered a significant pollutant for diesel engines, were achieved with the parameters investigated in this study. The obtained results were evaluated as promising in terms of developing dual-fuel combustion concepts.
Keywords: Alternative fuels: diethyl ether; Dual-fuel engines; Ethanol; Dual-direct injection